Captain Underpants and the attack of the talking toilets : another epic novel - Pilkey, Dav, 1966- (New York : Scholastic, 1999)
While sitting in detention, George and Harold accidentally create an army of evil talking toilets, and Principal Krupp's alter ego, Captain Underpants, has to save the world from it.
"Featuring flip-o-rama"--Cover p. [4].
Publisher's Weekly
School Library Journal
Wilson's Children
4.7
3-6.
Keywords: Captain Underpants (Fictitious character) -- Fiction; Cartoons and comics -- Fiction; Heroes -- Fiction; Humorous stories; School principals -- Fiction; Schools -- Fiction; Toilets -- Fiction; Captain Underpants (Fictional character) -- Fiction; Heroes and heroines -- Fiction; Humorous fiction; School stories; School superintendents and principals -- Fiction; Toilets -- Fiction